2021
DOI: 10.2478/mgrsd-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and perspectivesfor human activity in Arctic coastal environments – a review of selected interactions and problems

Abstract: The currently-observed increase in human activity in the Arctic accelerates the negative impact on the environment as well as increases the risk of threats to mankind itself. This paper reviews and summarises a selection of studies on the interaction between humans and the environment in the Arctic coastal zone, which is impacted by a warming climate and associated geohazards. The paper presents a general description of human presence in the Arctic, identifies and describes the processes that are threatening t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 113 publications
0
3
0
Order By: Relevance
“…It might be suggested that the absence of a clear correlation between coastal dynamics and environmental drivers is due to human interaction within the studied coastal zone. The technogenic impact may influence substantially both spatial and temporal patterns of coastal behavior [90][91][92][93]. Such human-triggered erosion of the Kara Sea coasts was observed in previous studies [11,76,94].…”
Section: Human Impactmentioning
confidence: 62%
“…It might be suggested that the absence of a clear correlation between coastal dynamics and environmental drivers is due to human interaction within the studied coastal zone. The technogenic impact may influence substantially both spatial and temporal patterns of coastal behavior [90][91][92][93]. Such human-triggered erosion of the Kara Sea coasts was observed in previous studies [11,76,94].…”
Section: Human Impactmentioning
confidence: 62%
“…Most of them focused on the evolution of the most dynamic processes of the coastline such as erosion/progradation of beaches or accumulation shapes. These processes are frequently monitored because they often affect marine traffic transportation facilities, industrial infrastructure (Jaskólski 2021) (Ziaja et al 2009) even though this calculated value is disputable regarding the geomorphologic settings of the locality. Such changes on a decadal timescale usually mean the absolute shift of the coastline in the order of tens to hundreds of meters.…”
Section: Context Within the Svalbard Archipelago And The Arcticmentioning
confidence: 99%
“…This impacts both endemic Arctic species and boreal visitor species (Hamilton et al, 2021); e.g., fin whales have recently been observed to change their observed presence in Arctic regions from late spring/early summer to the fall to year-round (Klinck et al, 2012). At the same time, human activities, their intensity, and impacts are also evolving with sea-ice loss; e.g., with the impending development of cross-Arctic shipping routes and openings for natural resource exploitation (Jaskolski, 2021;Townhill et al, 2022). Hence, we can expect that human activities will intensify in species-rich areas (Hamilton et al, 2021).…”
Section: Introductionmentioning
confidence: 99%